Effect of Maturation with American Oak Chips on the Volatile and Sensory Profile of a Cabernet Sauvignon Rosé Wine and Its Comparison with Commercial Wines - Miguel Ángel Hernández-Carapia; José Ramón Verde-Calvo; Héctor Bernardo Escalona-Buendía; Araceli Peña-Álvarez (Beverages, 2023)
Rosé wines are commonly consumed as young wines mainly due to their freshness and fruity character. Nevertheless, in recent years a new market looking for alternatives to traditional wines has emerged. Considering this, the study of the volatile and sensory profiles of a varietal rosé wine aged with oak chips was carried out. Two Cabernet Sauvignon rosé wines were made: one was maturated with oak chips and the other without. Both wines were physicochemically characterized. Then, their volatile and sensory profiles were analyzed, also including two commercial wines. The results showed that the produced wines complied with Mexican regulations. Also, they showed greater relative areas in compounds such as ethyl (E)-2-hexenoate, ethyl heptanoate, ethyl nonanoate, ethyl 3-nonenoate, β-citronellol, (±)-trans-nerolidol, and β-damascenone. In their sensory profile, they were mostly related to attributes such as berries, prune, bell pepper, and herbaceous notes. Among the compounds related to barrel maturation, only cis-oak-lactone was identified in the rosé wine matured with chips. However, it was associated with vanilla, woody, smoky, and spicy attributes. According to the results, the maturation of rosé wines with oak chips could be a good alternative to provide them with unusual notes and thus offer new alternatives to traditional and new wine consumers.